Presence of antibiotic resistance genes in a sewage treatment plant in Thibodaux, Louisiana, USA. (July 2015) - Naquin, Anthony; Shrestha, Arsen; Sherpa, Mingma; Nathaniel, Rajkumar; Boopathy, Raj
Highlights: Antibiotic resistance genes in the raw and treated sewage were demonstrated. mecA gene was present in both raw and treated sewage in all sampling events. Genetic transformation was demonstrated using the mecA gene found in sewage. Abstract: Increasing uses and disposals of antibiotics to the environment have increased emergence of various antibiotic resistance. One of the sources for the spread of antibiotic resistance is wastewater treatment plant, where bacteria and antibiotics can come in contact and can acquire antibiotics resistance. There are very few studies on this subject from a small town sewage treatment plant. Therefore, this study was conducted using raw sewage as well as treated sewage from a sewage treatment plant in Thibodaux in rural southeast Louisiana in USA. Samples were collected monthly from the Thibodaux sewage treatment plant and the presence of antibiotic resistance genes was monitored. The study showed the presence of antibiotic resistance genes in both raw and treated sewage in every month of the study period. The genetic transformation assay showed the successful transformation of methicillin resistant gene, mecA to an antibiotic sensitive Staphylococcus aureus, which became antibiotic resistant within 24 h.